Proses Komunikasi Antarpribadi Komunitas Kelas Mengajar Nusantara dalam Memotivasi Minat Belajar Anak-Anak di RPTRA Perdamaian Kebagusan - Rizon, Dwi Pharahdilla; Sinaiyangsih, Xaviera Ananda; Nuraini, Januar Salma; Azzahra, Yasmin Fatimah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The focus and objective of this study are to examine the interpersonal communication process among members of the Kelas Mengajar Nusantara Community in motivating children's learning interest at RPTRA Perdamaian Kebagusan. This research adopts the Social Penetration Theory approach, which includes five stages of communication: orientation, exploratory, affective, stable, and depenetration. The research employs a qualitative descriptive method with three key informants. Data were collected through in-depth interviews, observations, and documentation, then analyzed using an inductive approach to gain a deeper understanding of the communication dynamics involved. The findings indicate that members of the Kelas Mengajar Nusantara Community gradually apply communication stages in their interactions with children at RPTRA Perdamaian Kebagusan. Their communication process successfully creates an engaging learning environment, ultimately fostering children's interest in learning. However, several challenges arise in the implementation, including a limited number of teaching volunteers, uncertainty regarding the number of children attending each session, and varying levels of understanding among the children.